Avian influenza and upland gamebirds: Protection through biosecurity - Honeyfield, Amanda (My University, 2019)
In a world that grows ever smaller with the speed of innovation and trade, the spread of disease, specifically zoonotic disease, becomes an ever-looming threat to the health of society. One such disease is avian influenza (AI). Once primarily confined to Asia, AI has migrated with wild waterfowl to North America. AI strains are subdivided into two categories: high pathogenic avian influenza and low pathogenic avian influenza; this classification is based on the severity of the disease in chickens. While avian to human and human to human spread of AI is rare, scientists and public health officials are identifying AI in humans. AI has been isolated primarily in people who have been exposed to poultry. Human case fatality rates vary from outbreak to outbreak. The author describes her experience working with Dr. LewAnn Schneider with the USDA during the summer of 2018 and the variety of opportunities she participated in. She goes on to discuss her work in creating biosecurity plans for upland gamebird producers and some of the aspects of a good biosecurity plan. Some of the coursework the author completed as part of her degree are described and the advantages that each gave her.
Keywords: biosecurity; game birds; USDA; Avian Influenza